Urinary levels of monohydroxyl PAH metabolites in portuguese firefighters: background levels and impact of tobacco smoke - Oliveira, Marta (2016)
Firefighting occupational exposure is classified as possible carcinogen to humans by the International Agency for Research on Cancer and the US National Institute for Occupational Safety and Health [1,2].  Tobacco smoke is a very important factor in the assessment of occupational exposure of workers, since the prolonged exposure to tobacco smoke is by itself the major cause of lung cancer [3]. The consumption of tobacco is responsible for the exposure to many smoke components including more than sixty known carcinogens, including some polycyclic aromatic hydrocarbons (PAHs) [4].  PAHs are ubiquitous compounds formed during pyrolysis or incomplete combustion of organic matter, being well-known for their toxic, mutagenic, and carcinogenic properties to humans [5,6]. So far, the impact of tobacco smoke on firefighters’ total exposure to PAHs is very limited.